Towards Substantiation of Synergetic Public Management (taking labor market as example) - Sierikov , Anatolii (Theory and Practice of Public Administration, 2019)
The paper considers the specific situation in which the state of the regional economy is determined solely by the shortage of highly trained workers in the regional labor market. The preliminary analysis of the situation is accomplished by using the methodology of simulating cyclic causative diagrams. For a further, more detailed study of the situation, the mathematical model of the system "supply / demand" in the regional labor market is written in the form of a system of nonlinear differential equations of the first order. Analysis of the dynamics of the ratio "demand / supply" in this labor market indicates its imbalance. The latter can be overcome if regional authorities take advantage of the opportunities arising from the appearance of internally displaced persons (migrants or migrants) in the region. With their appearance there is an opportunity to replenish the labor market by professionally trained specialists, whose work there is demand from enterprises located in the region. Whatever the success of the authorities, it is necessary to further influence the situation, that is, to manage it. To this end, it is necessary to provide a series of measures to motivate both owners and top management of enterprises and migrants. The former may have, for example, opportunities to take advantage of tax privileges. The second is the spectrum of socio-economic incentives, namely: free education, affordable mortgage lending, and so on. At the expense of the above, a new system "demand / supply + management" with more degrees of freedom is created. But if its management is built on all the principles of the synergetic control theory, based on the principle of directed self-organization of nonlinear systems, by constructing positive inverse relationships in the system "demand / supply + management" it is possible to significantly reduce the number of degrees of freedom. The study of the dynamics of such a system proves the feasibility of the chosen control. As an "order parameter", which offers management, the motivational policy of power may be in the direction of employers and in the direction of migrant workers. As a result, the labor market can be balanced at a certain, pre-planned level, which will provide a boost to the recovery of the economy in the region.